2016
DOI: 10.15314/tjse.14670
|View full text |Cite
|
Sign up to set email alerts
|

Relative age effect in Turkish soccer

Abstract: Relative Age Effect (RAE) refers to the difference between the individuals who were born in the early or the later period of the same year. The purpose of this study was to investigate the existence and prevalence of RAE in Turkish Soccer. The data were collected from 3074 (530 professional players and 2544 amateur players) active players who play for eight different age categories of 19 soccer clubs in Turkish First Soccer League. The significance of the distributions by birth month, distributions by quarter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This finding could therefore support the general assumptions that the players born early in the year have presumably more experience and thus, account for their apparent dominance in any age-defined competitions. This argument could be supported by the preceding researchers who reported that the players born early in the year might be associated with considerably larger body size, higher muscle power, strength as well as motor competency when compared to their counterparts (da Costa et al, 2012;Helsen, Starkes, & Van Winckel, 1998;Mulazimoglu et al, 2016). These physical advantages pose a greater challenge for bridging the gap of RAE in sports, since older athletes are considered more talented by virtue of their physical attributes.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This finding could therefore support the general assumptions that the players born early in the year have presumably more experience and thus, account for their apparent dominance in any age-defined competitions. This argument could be supported by the preceding researchers who reported that the players born early in the year might be associated with considerably larger body size, higher muscle power, strength as well as motor competency when compared to their counterparts (da Costa et al, 2012;Helsen, Starkes, & Van Winckel, 1998;Mulazimoglu et al, 2016). These physical advantages pose a greater challenge for bridging the gap of RAE in sports, since older athletes are considered more talented by virtue of their physical attributes.…”
Section: Discussionmentioning
confidence: 81%
“…In other words, the athletes born at the beginning of the cut-off month tend to outperform their peers. These effects have been established in a varying number of sports in which the proportion of the birth date is largely skewed in favor of the athletes born at the beginning of the selection year (Cobley, Baker, Wattie, & McKenna, 2009;McCarthy, Collins, & Court, 2016;Mulazimoglu, Bayansakduz, Kaynak, & Mulazimoglu, 2016). However, it should be noted that RAE is likely to be more pronounced in physically demanding sports, in which the athletes born at the beginning of the selection year possess a physical edge over their counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted by Mulazimoglu (Mulazimoglu, Bayansalduz, Kaynak & Mulazimoglu, 2016), Turkish Football Federation affiliated league in which they are born in the first quarter of 48.22% of the players who played in the U14 category, indicated that 10.96% of them were born in the last quarter of the year, The ratios of 14-year-old soccer players who were born in January and December were found to be statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…In sport, the RAE describes "The relationship observed between an individual's month of birth relative to their peers and their achievement in sports (Reed et al, 2017). Relative age can be associated with several features such as strength, endurance and sport-related technique (Cobley et al, 2009;Delorme, Boiche, & Raspaud, 2010;Mulazimoglu, Bayansalduz, Kaynak & Mulazimoglu, 2016;Sierra-Diaz et al, 2017). It is quite significant particularly in the branches in which body size, power and strength are very important (Cobley et al, 2009).…”
Section: Introductionmentioning
confidence: 99%